Incidence of glucose level abnormalities in neonatal sepsis and its association with mortality - Parvathi, K. S. L.; Soma, Santosh Kumar; Thanda, Prasad (International Journal of Contemporary Pediatrics, 2020)
Background: Plasma glucose abnormalities were previously noted in neonatal sepsis, but data in neonates is limited and the association with mortality is not established. The aim of the study was to determine the incidence of plasma glucose abnormalities among newborns with sepsis and their association with mortality. Methods: This was a prospective observational study including 50 neonates with suspected, probable and proven sepsis. Plasma glucose level was measured within 2 hours of admission and the patients were monitored till discharge or death. The patients were divided into hyperglycaemic, hypoglycaemic and normoglycemic subgroups as per the serum glucose levels. Results: Majority (56%) were noted to have normoglycemia, followed by hypoglycaemia in 32% and 12% had hyperglycaemic. Mortality in the hypoglycemic, hyperglycemic, and normoglycemic subgroups were 50.0, 33.3, and 7.2% respectively. Mortality was high in hyperglycemic patients compared to normoglycemic patients but the difference was not statistically significant between two groups, whereas the mortality was high in hypoglycemic patients compared to normoglycemic patients and the difference was statistically significant between two groups. A significant association was noted between hypoglycemia in neonatal sepsis with mortality. Conclusions: Altered glycemic status is common in neonatal sepsis. Mortality is higher among septic neonates with hypoglycemia. We conclude that majority of septic neonates had high mortality rate when plasma glucose levels were either >145 mg/dl or <45 mg/dl. This signifies the importance of plasma glucose estimation in cases of neonatal sepsis to improve mortality outcome.